Об оценке эффективности оптимизационных метаэвристических стратегий - Пепеляев, В.А. (Теорія оптимальних рішень, 2006)
One of the possible approaches to estimate the effectiveness of metaheuristic optimization strategies implemented in the framework of the integrated simulation environments is proposed. Concerning simulation applications developed in simulation-optimization system NEDOPT the procedures to estimate the above strategies' effectiveness are considered.